2018
DOI: 10.1039/c8ta04993a
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic optimization of carrier transport and thermal conductivity in Sn-doped Cu2Te

Abstract: Doping Sn into the Cu2Te lattice can synergistically enhance the power factor and decrease thermal conductivity, leading to remarkably optimized zTs. The lone pair electrons from the 5s orbital of Sn can increase the DOS near the Fermi level of Cu2Te to promote PF and reduce κe by decreasing the carrier concentration. This study explores a scalable strategy to optimize the thermoelectric performance for intrinsically highly degenerate semiconductors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 47 publications
5
13
0
Order By: Relevance
“…Additionally, dynamic cation disorder decreases lattice thermal conductivity, and an impressive zT ∼ 1.6 at 670 K was obtained in Se doped AgCuTe [52]. Similarly, Sn doping has been used to tune the high hole concentration of Cu 2 Te and zT ∼ 1.5 has been achieved at 1000 K [53]. A mosaic crystal of Cu 2 (Te,S) has also been reported with zT ∼ 2.09 at 1000 K [54].…”
Section: Transition Metal (Tm) Telluridesmentioning
confidence: 95%
“…Additionally, dynamic cation disorder decreases lattice thermal conductivity, and an impressive zT ∼ 1.6 at 670 K was obtained in Se doped AgCuTe [52]. Similarly, Sn doping has been used to tune the high hole concentration of Cu 2 Te and zT ∼ 1.5 has been achieved at 1000 K [53]. A mosaic crystal of Cu 2 (Te,S) has also been reported with zT ∼ 2.09 at 1000 K [54].…”
Section: Transition Metal (Tm) Telluridesmentioning
confidence: 95%
“…In recent years, various strategies have been proposed to enhance the ZT values of materials, such as band engineering, nanostructure engineering, nano-composite structures, secondary-phase incorporation, and the “phonon-glass electron-crystal” (PGEC) paradigm . Among these approaches, the PGEC is a very effective and popular approach to enhance TE properties of materials, which could reduce the lattice thermal conductivity by enhancing phonon scattering without sacrificing electronic transport properties.…”
Section: Introductionmentioning
confidence: 99%
“…The carrier mobility in Cu 2 Te was found to be ∼50−100 cm 2 V −1 s −2 which is greater than those in Cu 2 S (<10 cm 2 V −1 s −2 ) and Cu 2 Se (∼20−40 cm 2 V −1 s −2 ) in the temperature range 50− 300 K. 21 Copper telluride is represented with simple molecular formula Cu 2−x Te, but it shows a quite complex atomic arrangement and forms different phases such as CuTe, Cu 2−x Te, and Cu 2 Te. 33,27,34 The compound has vast technological applications such as solar cells 25,28,6 and fast switches and TE generators; 2,21,26 however, the existence of a variety of polymorphic forms and phases of copper telluride makes understanding of the fundamental properties, such as crystal structure, electronic band structure, phonon dispersion, and phonon−phonon interactions, challenging and thus they remain unexplored. Further, CT also shows a structural phase transition with temperature.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Recently, superionic Cu 2– x X (X = S, Se) are reported to have ultralow κ and high zT due to the liquid-like behavior of Cu ions around the crystalline sublattice of X and are considered as a new class of phonon–liquid–electron–crystals (PLEC). ,, ,,, Further, the superionic CT2 has an interesting structure where the tellurium atom forms a rigid sublattice and the liquid-like Cu ions are distributed randomly in the rigid sublattice and thus classified as PLEC . It has been observed that several state of the art TE materials are tellurides, such as PbTe, SnTe, ,, and Bi 2 Te 3 , , and have better performances than their Se and S counterparts. ,, Thus, the present work focuses on the Raman spectroscopic studies of copper tellurides.…”
Section: Introductionmentioning
confidence: 99%